(untitled) (Revista científica Olimpia, 2020)
The item has to explain the importance of educational work at the university with examples ISEFD (Higher Institute do Physical Education and Sport). The answer to six questions it to develop the theme of educational work, and implementation in three dimensions: curricular, extension and social. In the formation of the personal, more competent, with ethics that can improve the values in all spheres of the action. The importance of didactics in higher education, where it is not enough just to have mastery of the subjects to de taught, but also to have didactics in transmitting and educating values. The didactic proposal of the educational project is made on how to educate values in the physical education and sport of ISEFD, I am a way of acting and strategic actions to guarantee to educate values and their way of acting. The purpose of the proposal is to socialize and to be implemented in other institutions